Cyber-risks from using IoT devices for managing COVID-19 - Radanliev, P; De Roure, D; Van Kleek, M (IEEE IoT Newsletter, 2021)
Scientific research is increasingly focused on COVID-19 management with IoT technologies and artificial intelligence (AI). Autonomous connected devices, performing medical tasks without physical human interaction, is certainly beneficial for treating deadly infectious pandemics. Some examples of medical IoT solutions include thermal camera detection monitoring for COVID-191 , connected thermometers, smart wearables, and even IoT buttons for COVID-19 emergencies2 . Although the current focus is predominated with COVID-19 mobile tracing apps3 , the IoT technologies are currently tested for advanced long-term healthcare solutions. Some of the current applications include patients desk sensors in field hospitals built for COVID-19, remote temperature monitoring of medical units, and open/close sensors for monitoring for restricted areas4 . Long-term solutions are crucial for preventing and managing future pandemics, and for post-COVID-19 strategic digital transformations, in anticipation of ‘COVID-21’5 . However, COVID-19 has already exposed significant cyber-risks on medical IoT systems, and two US hospitals have been attacked, exploiting vulnerabilities in medical IoT devices6 . Such cyber-attacks could hinder the adoption of IoT solutions for long term pandemic management planning. Since IoT can provide unique solutions for COVID-19 management, its safe adoption in long term solutions seems of utmost importance. In the following, we review how cyber-risk from medical IoT solutions could be assessed, in a fast-changing global pandemic.